Highly selective transmission success of dengue virus type 1 lineages in a dynamic virus population : an evolutionary and fitness perspective - Koo, Carmen (2019)
Arbovirus transmission is modulated by host, vector, virus, and environmental factors. Even though viral fitness plays a salient role in host and vector adaptation, the transmission success of individual strains in a heterogeneous population may be stochastic. Our large-scale molecular epidemiological analyses of a dengue virus type 1 population revealed that only a subset of strains (16.7%; n = 6) were able to sustain transmission, despite the population being widely dispersed, dynamic, and heterogeneous. The overall dominance was variable even among the “established” lineages, albeit sharing comparable evolutionary characteristics and replication profiles. These findings indicated that virological parameters alone were unlikely to have a profound effect on the survival of viral lineages, suggesting an important role for non-viral factors in the transmission success of lineages. Our observations, therefore, emphasize the strategic importance of a holistic understanding of vector, human host, and viral factors in the control of vector-borne diseases.